Cationic Cyclodextrin-Based Carriers for Drug and Nucleic Acid Delivery - Adila Nazli; Milo Malanga; Tamás Sohajda; Szabolcs Béni (Pharmaceutics)
Cyclodextrins can serve as carriers for various payloads, utilizing their capacity to form unique host–guest inclusion complexes within their cavity and their versatile surface functionalization. Recently, cationic cyclodextrins have gained considerable attention, as they can improve drug permeability across negatively charged cell membranes and efficiently condense negatively charged nucleic acid due to electrostatic interactions. This review focuses on state-of-the-art and recent advances in the construction of cationic cyclodextrin-based delivery systems. First, we identified different cationic moieties that are commonly employed in the design of cyclodextrins with enhanced complexation ability. Subsequently, a wide range of cationic cyclodextrin-based drug delivery systems were analyzed with emphasis on chemistry, drug release profiles, and therapeutic outcomes. The evaluation of the delivery platforms was also based on the four major types of drugs, such as anticancer, anti-inflammatory, antibacterial, and antidiabetic agents. The delivery systems for nucleic acids were also summarized while focusing on their condensation ability, transfection efficiency, and biocompatibility in comparison to commercially available vectors such as PEI 25 kDa and lipofectamine 2000. Furthermore, we highlighted the potential of cationic cyclodextrins in constructing multimodal delivery systems for the simultaneous encapsulation of both drugs and nucleic acids. Finally, the challenges and limitations associated with cationic cyclodextrin setups were discussed.